2012
DOI: 10.1017/s0007114511007185
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose menaquinone-7 supplementation improved extra-hepatic vitamin K status, but had no effect on thrombin generation in healthy subjects

Abstract: Vitamin K is required for the carboxylation of Gla-proteins in the liver (coagulation factors) and extra-hepatic tissues, such as bone (osteocalcin, OC), and arterial wall (matrix Gla-protein, MGP). Although the coagulation factors are essentially fully carboxylated under normal conditions, 10-40 % of OC and MGP remains undercarboxylated. We were therefore interested to study the dose -response effects of extra intake of menaquinones on the carboxylation of the extra-hepatic Gla-proteins. A total of forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 14 publications
4
83
0
4
Order By: Relevance
“…Elevated concentrations of ucOC are associated with vitamin K deficiency and an increased risk of hip fractures [5,13,14,35,36]. Supplementation with vitamin K 2 promotes a decrease in ucOC, suggesting that vitamin K 2 contributes to OC carboxylation [9,37]. In the functional study, we observed that synthetic and fermentation-derived MK-7 gave similar steady-state serum concentrations of MK-7, and had similar abilities to reduce the serum ucOC concentration, although the reduction from baseline in the fermentation-derived MK-7 group was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of ucOC are associated with vitamin K deficiency and an increased risk of hip fractures [5,13,14,35,36]. Supplementation with vitamin K 2 promotes a decrease in ucOC, suggesting that vitamin K 2 contributes to OC carboxylation [9,37]. In the functional study, we observed that synthetic and fermentation-derived MK-7 gave similar steady-state serum concentrations of MK-7, and had similar abilities to reduce the serum ucOC concentration, although the reduction from baseline in the fermentation-derived MK-7 group was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the few studies of MK7, 360mcg/d reduced ucOC and increased cOC in early postmenopausal women 75 , although a lower dose may also be effective in increasing cOC 9,55 . Nevertheless, reduction of serum ucOC is not always accompanied by improvement in BMD 76 .…”
Section: Bonementioning
confidence: 98%
“…Menaquinone may take 14 different forms, of which MK4 and MK7 are the most studied, with high quantities of MK7 found in the Japanese food natto, made from fermented soy. Both forms of vitamin K can function as enzyme cofactors in the γ-carboxylation of glutamic acid residues to produce the calcium-binding γ-carboxyglutamate (Gla) proteins, which impact blood coagulation, CV calcification and bone formation, with the mechanisms for all three being similar 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin K2 intake seems to be the most appropriate strategy to prevent chronic vitamin K insufficiency, and a dietary intake of 45 mcg/day has been reported to have significant health benefits in population-based studies. In dose-response experiments, a supplement of 45-90 µg/day induced a significant decrease of circulating dp-ucMGP levels, demonstrating improvement of extrahepatic vitamin K status [48][49][50]. This amount is obtained by the consumption of 70-100 grams of cheese per day.…”
Section: Eumentioning
confidence: 99%